Exploring the Type III Secretion System in Shigella flexneri: from Biotin Ligase Optimization to IpgC Proxisome Profiling - Haidar Ahmad, Nathaline (Université d'Ottawa | University of Ottawa, 2025)
Shigella flexneri remains a major global health concern, causing tens of millions of infections and hundreds of thousands of deaths annually. Central to the pathogenesis of S. flexneri is the Type III Secretion System (T3SS), a nanomachine that translocates effector proteins into host cells to invade them. The T3SS undergoes major structural and functional rearrangements upon activation, yet many of the protein interactions and changes associated with this system remain poorly defined due to their transient and dynamic nature. To address this, we adapted the biotin ligase TurboID proximity labeling system for use in S. flexneri, optimizing it to function efficiently in the bacterial cytoplasm. TurboID exhibited rapid biotinylation kinetics and minimal cross-reactivity with native BirA binding partners, making it well suited for mapping protein proxisomes and interactomes in Shigella. We applied this system to two key proteins of the T3SS transcriptional cascade: IpgC, a dual-function chaperone and co-activator, and MxiE, the AraC-family transcription factor that controls late effector gene expression such as the IpaHs. Using IpgC and MxiE as baits, we profiled their proxisomes in both T3SS on and off-states. Our results confirmed established MxiE-IpgC interactions and identified novel candidate partners, including transcription factors and metabolic enzymes, suggesting a broader regulatory network. Notably, we found that IpgC’s proxisome extends beyond the T3SS, pointing to unexplored roles. For example, our data also suggests that IpgC may play a role in modulating acid stress responses. These results provide new insights into the regulatory complexity of the T3SS and serve as a platform for uncovering novel protein interactions, paving the way for future studies on T3SS regulation and antivirulence therapies. Our findings also underscore the utility of biotin ligases for studying protein complexes in Shigella and other bacterial models.
Keywords: Shigella; T3SS; T3SA; BioID2; TurboID; BioID; Biotin ligases; Proximity labeling; Proxisome